The positive allosteric modulator of the mGlu2 receptor JNJ-46356479 partially improves neuropathological deficits and schizophrenia-like behaviors in a postnatal ketamine mice model. (July 2020) - Martínez-Pinteño, Albert; García-Cerro, Susana; Mas, Sergi; Torres, Teresa; Boloc, Daniel; Rodríguez, Natalia; Lafuente, Amalia; Gassó, Patricia; Arnaiz, Joan Albert; Parellada, Eduard
Abstract: Current antipsychotics have limited efficacy in controlling cognitive and negative symptoms of schizophrenia (SZ). Glutamatergic dysregulation has been implicated in the pathophysiology of SZ, based on the capacity of N-methyl-D-aspartate receptor (NMDAR) antagonists such as ketamine (KET) to induce SZ-like behaviors. This could be related to their putative neuropathological effect on gamma-aminobutyric (GABAergic) interneurons expressing parvalbumin (PV), which would lead to a hyperglutamatergic condition. Metabotropic glutamate receptor 2 (mGluR2) negatively modulates glutamate release and has been considered a potential clinical target for novel antipsychotics drugs. Our aim was to evaluate the efficacy of JNJ-46356479 (JNJ), a positive allosteric modulator (PAM) of the mGluR2, in reversing neuropathological and behavioral deficits induced in a postnatal KET mice model of SZ. These animals presented impaired spontaneous alternation in the Y-maze test, suggesting deficits in spatial working memory, and a decrease in social motivation and memory, assessed in both the Three-Chamber and the Five Trial Social Memory tests. Interestingly, JNJ treatment of adult mice partially reversed these deficits. Mice treated with KET also showed a reduction in PV+ in the mPFC and dentate gyrus together with an increase in c-Fos expression in this hippocampal area. Compared to the control group, mice treated with KET + JNJ showed a similar PV density and c-Fos activity pattern. Our results suggest that pharmacological treatment with a PAM of the mGluR2 such as JNJ could help improve cognitive and negative symptoms related to SZ. Highlights: JNJ-46356479 improve cognitive and negative symptoms related to schizophrenia. Mice model for the negative symptoms of schizophrenia, ketamine on PND 7, 9 and 11. Characterization of schizophrenia-like behavior in adulthood. Neuronal changes in the prefrontal cortex and hippocampus.